THE EFFECT OF JOB EMBEDDEDNESS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR: The Mediating Role of Sense of Responsibility - Wijayanto, Bonifacius Riwi; Kismono, Gugup (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
This study examines a new attachment concept called job embeddedness as antecedent of organizational citizenship behavior (OCB). Firstly, we tested hypothesis concerning positive relationship between job embeddedness and OCB as predicted by Mitchell et al. (2001). Secondly, we tested hypothesis concerning the mediation effect of sense of responsibility in the relationship between job embeddedness and OCB.Nurses (N = 170) and their immediate supervisors ( N = 41) from five privately owned hospital in Jogjakarta participated in this study. Of 340 questionnaires distributed to the respondents, 339 were returned yielding a response rate of 99 percent. Of those returned, 300 questionnaires were available for further analyses. Nurses were asked to respond to a questionnaire of 40 items concerning perception of embeddedness and 4 item concerning sense of responsibility to their employing organization. Nursesâ citizenship behavior were measured using 12 items as rated by their immediate supervisors. The results support the hypothesis that job embeddedness correlates positively with OCB. However, our result failed to support the prediction of the mediating effect of employeesâ sense of responsibility in causal relationship between job embeddedness and OCB. The implications of the findings for further research on relationship between job embeddedness and OCB research are discussed.